Longitudinal trajectories of identity formation and resilience development in adolescents living in disadvantaged communities - Shirima, Catherine M. (University of the Free State, 2022)
Transitioning to adulthood is a core task which requires of adolescents to work on defining their sense of self. Indeed, they have to overcome an identity crisis in order to establish a coherent sense of self. Consequently, resilience becomes of uttermost importance for their wellbeing. In essence, identity and resilience are crucial processes of focus in their development. The urgency of the issue applies likewise to South African adolescents who are faced with unique challenges. Therefore, this study examined longitudinal trajectories of identity formation based on the five-dimensional model of identity development and explored resilience as it pertains to adolescents living in disadvantaged communities of South Africa. An equal weight, concurrent mixed methods research approach with a longitudinal design was used in this study. A non-probability convenience sampling technique was employed to collect quantitative data, and a purposive sampling technique was used to collect qualitative data. The final sample for the quantitative approach consisted of 564 participants aged between 12 and 24 years. For the qualitative data, a total of 18 groups with 162 participants aged between 14 and 21 contributed to focus group interviews. Data were collected over three points in time (in intervals of six months). The data for this study were collected using the Dimensions of Identity Development Scale (DIDS), and the Resilience Questionnaire for Middle-Adolescents in Township Schools (R-MATS). A semi structured interview schedule was used to guide the focus group interviews. Given the longitudinal nature of the study, repeated measures analyses of variance (ANOVA) allowed the examination of associations between the dimensions of identity and resilience across different points in time. Qualitative data were analysed using a hybrid approach of inductive and deductive reflexive thematic analyses. The study results indicated no significant time effect on the identity dimensions; the dimensions of identity showed a stable trajectory. There was a significant difference in some aspects of resilience across the points in time. Considering the interaction between identity and resilience, results indicated significant findings for Exploration in Depth, with the high resilience group showing a significant decrease in Exploration in Depth over time and the low resilience group a gradual increase. Although previous studies have shown the connection between resilience and identity, in this study the novelty is only directed to Exploration in Depth and resilience. Participants’ experiences of identity and resilience over time were thematically analysed, and four main themes were generated. The first related to participants’ experiences of who they are in trying to find a balance between individual attributes and resilience. The second pertained to risks and opportunities detailing the complexity in exploring resilience, while a third was participants’ experiences of agency when faced with adversity. Finally, the fourth theme highlighted the role of significant others and religious beliefs in navigating through landmines of life. Results demonstrated the important role of agency in pursuit of future directions. It was apparent that the participants in this study, played a significant role in shaping their lived experiences in relation to their identity formation and resilience. Furthermore, the participants' interactions with others were prominent in facilitating their understanding of who they are and their ability to deal with hardships, since those interactions gave them a sense of acceptance, belonging, and assurance and they did not feel judged. Participants’ ability to recognise available structures and to actually make use of them in the process of their identity development and resilience was evident in this study.
Thesis (Ph.D (Psychology))--University of the Free State, 2022
Keywords: Adolescents; identity; resilience; disadvantaged background; longitudinal; mixed methods research